Influence of Sexual Function on the Social Relations and Quality of Life of Women with Premature Ovarian Insufficiency - Daniela Angerame Yela; Patricia Magda Soares; Cristina Laguna Benetti-Pinto (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2018)
Abstract Objective To evaluate the impact of sexual function (SF) in the quality of life (QoL) of women with premature ovarian insufficiency (POI). Methods Case-control study in which 80women with POIwere evaluated using estrogen plus progestogen therapy, compared with 80 women matched by age (2 years) and presenting preserved gonadal function. Sexual function was evaluated using the Female Sexual Function Index (FSFI), and the QoL was evaluated using theWorld Health Organization's (WHO) QoL assessment instrument (WHOQoL-BREF). Results The mean age of the women with POI and of the control group was 38.4 ± 7.3 years and 38.1 ± 7.3 years respectively. The QoL, was worse among the POI group, and there were significant differences in the physical (63.4 ± 17.4 and 72.7 ± 15.2 respectively, p = 0.0004) and psychological (63.2 ± 14.6 and 69.3 ± 13.9 respectively, p = 0.0075) domains among this group when compared with the control group. Women with POI presented significantly lower arousal, lubrication, orgasm and satisfaction, more dyspareunia and a worse FSFI scores when compared with the control group. All aspects of SF correlate directly with the worsening of the QoL regarding social relationships. Conclusion Women with POI showed worse QoL and SF than the control group. The psychological aspects (desire, excitement, orgasm and sexual satisfaction) of SF had greater influence on the parameters of the QoL, while the physical aspects (pain and lubrication) had a low impact on the QoL. The poor SF in women with POI is directly correlated with a worsening acrossmultiple domains of the QoL; however, the negative impact is particularly important in the social domain. These results suggest that the improvement in sexuality can improve the social interactions of women with POI.